2019
DOI: 10.1074/jbc.ra118.006319
|View full text |Cite
|
Sign up to set email alerts
|

Benzene-induced mouse hematotoxicity is regulated by a protein phosphatase 2A complex that stimulates transcription of cytochrome P4502E1

Abstract: Edited by Joel M. GottesfeldChronic benzene exposure is associated with hematotoxicity and the development of aplastic anemia and leukemia. However, the signaling pathways underlying benzene-induced hematotoxicity remain to be defined. Here, we investigated the role of protein phosphatase 2A (PP2A) in the regulation of benzeneinduced hematotoxicity in a murine model. Male mice with a hepatocyte-specific homozygous deletion of the Ppp2r1a gene (encoding PP2A A␣ subunit) (HO) and matched wildtype (WT) mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…These results indicated that the benzene-exposed workers in this study were at low levels of benzene exposure and suffered no significant hematotoxicity. Whereas urinary SPMA was a sensitive biomarker reflecting low levels of benzene exposure, similar results were also found in both animals or populations from previous low-level benzene toxicity studies ( 25 , 26 ). An epidemiological study confirmed that, at airborne benzene concentrations < 1 ppm, the WBC counts of benzene-exposed workers were within the normal range (4 × 10 9 /L to 10 × 10 9 /L) for clinical diagnosis, but their renewal and differentiation of hematopoietic stem cells (HSCs) had been significantly restrained ( 3 ).…”
Section: Discussionsupporting
confidence: 81%
“…These results indicated that the benzene-exposed workers in this study were at low levels of benzene exposure and suffered no significant hematotoxicity. Whereas urinary SPMA was a sensitive biomarker reflecting low levels of benzene exposure, similar results were also found in both animals or populations from previous low-level benzene toxicity studies ( 25 , 26 ). An epidemiological study confirmed that, at airborne benzene concentrations < 1 ppm, the WBC counts of benzene-exposed workers were within the normal range (4 × 10 9 /L to 10 × 10 9 /L) for clinical diagnosis, but their renewal and differentiation of hematopoietic stem cells (HSCs) had been significantly restrained ( 3 ).…”
Section: Discussionsupporting
confidence: 81%
“…It has been shown that Cer d18:1/18:0 influences protein phosphatase 2A (PP2A) activity [27]. PP2A is involved in the transcriptional regulation of CYP2E1 and might contribute to the liver toxicity of AOM [28]. The transforming growth factor β (TGFβ) signaling pathway has also been shown to be involved in AOM-related liver toxicity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our data also do not rule out Wnt-mediated control of neurogenesis via alternate downstream Wnt signaling pathways, such as the calcium or planar cell polarity pathways, or Wnt-mediated effects on circuit function that do not involve neurogenesis. Finally, although XAV939 has been shown to be selective for the Wnt pathway and to not affect the CRE (cAMP response element), NF-kB (nuclear factor kappa-light-chain-enhancer of activated B cells), or TGFb (transforming growth factor beta) pathways in reporter lines [25], and was effective in both in vivo and in vitro assays involving mice and neural cell types at the same dose used in this study [3739], unexpected off-target drug effects must still be considered.…”
Section: Discussionmentioning
confidence: 99%
“…XAV939 (Millipore Sigma) was dissolved in filter-sterilized 10% DMSO / 45% saline / 45% poly-ethylene glycol-400 (Affymetrix) at a final concentration of 1mg/ml. Animals received intraperitoneal injections daily for 14 days with vehicle or XAV939 (5 mg/kg) after recovery from surgery, as this dose effectively inhibits beta-catenin signaling in translational models [3739].…”
Section: Methodsmentioning
confidence: 99%